The semantic component of the evoked potential of differentiation - Korshunova, Svetlana G.; Izmailov, Chingis A.; Sokolov, Yevgeniy N. (The Spanish Journal of Psychology, 2008)
This work analyzes data from recordings of (occipital and temporal) cortical evoked potentials (called evoked potentials of differentiation (EPD) occurring in humans in response to an abrupt substitution of stimuli. As stimuli we used three groups of words: the names of the ten basic colors taken from Newton’s color circle; the names of seven basic emotions forming Shlossberg’s circle of emotions; and seven nonsense words comprised of random combinations of letters. Within each group of word stimuli we constructed a matrix of the differences between the amplitudes of mid-latency components of EPD for each pair of words. This matrix was analyzed using the method of multidimensional scaling. As a result of this analysis we were able to distinguish the semantic and configurational components of EPD amplitude. The semantic component of EPD amplitude was evaluated by comparing structure of the data obtained to the circular structures of emotion and color names. The configurational component was evaluated on the basis of the attribute of word length (number of letters). It was demonstrated that the semantic component of the EPD can only be detected in the left occipital lead at an interpeak amplitude of P120-N180. The configurational component is reflected in the occipital and temporal leads to an identical extent, but only in the amplitude of a later (N180-P230) component of the EPD. The results obtained are discussed in terms of the coding of categorized, configurational, and semantic attributes of a visual stimulus.
Keywords: Evoked potential of differentiation; Multidimensional scaling; Semantic component of EPD; Visual categorization